2007
DOI: 10.5459/bnzsee.40.1.18-24
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary reconnaissance report for the Kashmir earthquake of 8 October 2005

Abstract: A magnitude (Mw) 7.6 earthquake occurred at 8.55 am (local time) on 8 October 2005 causing extensive damage to buildings, bridges and roads and killing in excess of 87,000 people in the Kashmir region of northern Pakistan. Damage and deaths were also reported from Indian Administered Kashmir and eastern Afghanistan. The most severely affected region was in the epicentral area around Muzaffarabad in Pakistan Administered Kashmir. Reverse or thrust fault rupture on or near the Main Boundary Thrust of the Himalay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…According to Kamp et al (2008), bedrock lithology (comprising highly fractured slate, shale, dolomite, limestone and clastic sediments) was the most important landslide controlling parameter during the 2005 Kashmir earthquake. Dellow et al (2007) reported a highly asymmetric size and distribution of 2005 Kashmir earthquake induced landslides. According to this last paper, the landslides can be classified into the following three types: (1) landslides formed over/adjacent to the fault rupture,…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kamp et al (2008), bedrock lithology (comprising highly fractured slate, shale, dolomite, limestone and clastic sediments) was the most important landslide controlling parameter during the 2005 Kashmir earthquake. Dellow et al (2007) reported a highly asymmetric size and distribution of 2005 Kashmir earthquake induced landslides. According to this last paper, the landslides can be classified into the following three types: (1) landslides formed over/adjacent to the fault rupture,…”
mentioning
confidence: 99%
“…And as mentioned earlier, Shafique et al (2008) compared the aspect of landslides relative to the initial rupture point and found that about 80% of the landslides had an aspect facing away from the rupture point. In summary, the major controlling factors for 2005 Kashmir earthquake induced landslides were (1) human activity (Owen et al, 2008), (2) bedrock lithology (Kamp et al, 2008), (3) proximity with reference to fault trace (Dellow et al, 2007) and (4) slope direction with respect to source (Shafique et al, 2008). In our study, we analyzed landslide aspects with respect to the point of maximum release of energy (CMT solution).…”
mentioning
confidence: 99%
“…According to Kamp et al (2008), bedrock lithology (comprising highly fractured slate, shale, dolomite, limestone and clastic sediments) was the most important landslide controlling parameter during the 2005 Kashmir earthquake. Dellow et al (2007) reported a highly asymmetric size and distribution of 2005 Kashmir earthquake induced landslides. According to this last paper, the landslides can be classified into the following three types: (1) landslides formed over/adjacent to the fault rupture, (2) landslides which extend about 10-20 km from the fault trace on the hanging side of the fault and (3) landslides on the footwall side which are generally rare except within 2-3 km of the fault trace.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered to be the first Himalayan earthquake that was accompanied by surface rupture, reactivating the Muzaffarabad Fault (MF) (Figure 2.1) and, locally, offsetting the MBT (Hussain et al, 2009). Field investigations (Yeats et al, 2005;Kumahara and Nakata, 2006;Dellow et al, 2007;Kaneda et al, 2008) revealed a surface rupture60-70 km long, with up to 7 m vertical separation, mostly along the pre-existing MF.…”
Section: Kashmir Earthquakementioning
confidence: 99%
See 1 more Smart Citation